Growth of white shrimp post-larvae immersed in recombinant fish growth hormone - Laksana, Dita Puji; Subaidah, Siti; Junior, Muhammad Zairin; Alimuddin, ,; Carman, Odang (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT This research was conducted to determine the optimum immersion time of recombinant giant grouper growth hormone (Ephinephelus lanceolatus; rElGH) at a dose of 15 mg/L that generated highest growth of white shrimp post-larvae (PL). PL was bath-immersed for one, two, and three hours. Two types of control was provided, namely it was without any treatment (control), and immersion in water containing 0.01% bovine serum albumin (BSA) and total protein of Escherichia coli without rElGH (pCold control). All treatments and controls were consisted of three replications. A total of 1,500 PL-2 shrimp were bath-immersed in a plastic packing containing 1 L of sea water, 15 mg/L rElGH, and 0.01% BSA. PL was further reared for 21 days in the 60 L glass aquarium, and fed nauplii Artemia two times and flake commercial diet five times daily, at satiation. The results showed that the highest of biomass (36.29±1.46 g), specific growth rate (29.81±0.87%/day), and body length (20.08±0.42 mm) were obtained in three hours immersion treatment (P<0.05). Biomass of PL in three hours immersion treatment was approximately 66.0% higher compared to the control (21.87±2.53 g). Survival of shrimp in all treatment and control were similar (P>0.05). Thus, growth of white shrimp PL could be improved by bath immersion for three hours in rElGH solution of 15 mg/L water. Keywords: recombinant growth hormone, different immersion time, Pacific white shrimp, biomass  ABSTRAK Penelitian ini dilakukan untuk menentukan lama waktu perendaman hormon pertumbuhan rekombinan ikan kerapu kertang (Ephinephelus lanceolatus; rElGH) dosis 15 mg/L yang menghasilkan pertumbuhan tertinggi pada pascalarva (PL) udang vaname. Perendaman PL dilakukan satu, dua, dan tiga jam. Dua jenis kontrol dibuat yakni udang vaname PL-2 tidak diberi perlakuan (kontrol), dan direndam dalam air mengandung serum albumin sapi (BSA) 0,01% dan protein Escherichia coli tanpa rElGH (kontrol pCold). Setiap perlakuan dan kontrol diberi tiga ulangan. Sebanyak 1.500 ekor PL-2 direndam dalam kantong plastik kemasan berisi 1 L air laut mengandung rElGH 15 mg/L, dan BSA 0,01%. Selanjutnya, udang dipelihara selama 21 hari di dalam akuarium volume 60 L, dan diberi pakan naupli Artemia sebanyak dua kali dan pakan komersial berbentuk flake sebanyak lima kali sehari hingga kenyang. Hasil penelitian menunjukkan bahwa biomassa (36,29±1,46 g), pertumbuhan bobot spesifik (29,81±0,87%/hari), dan panjang tubuh (20,08±0,42 mm) tertinggi diperoleh pada perlakuan perendaman selama tiga jam (P<0,05). Biomassa udang perlakuan perendaman selama tiga jam lebih tinggi 66% dibandingkan dengan kontrol (21,87±2,53 g). Kelangsungan hidup udang yang direndam dengan rElGH, kontrol dan kontrol pCold tidak berbeda nyata (P<0,05). Dengan demikian, pertumbuhan PL udang vaname dapat ditingkatkan melalui perendaman selama tiga jam dalam larutan rElGH 15 mg/L air. Kata kunci: hormon pertumbuhan rekombinan, lama perendaman, pascalarva udang vaname, biomassa